Content evaluation of Islamic websites - Mahmud, Murni; Md. Tap, Abu Osman; Hussein, Idyawati; Aliyu, Mansur (2012)
This paper reports the user experience evaluation of four selected Islamic websites by Muslim users. The challenge of the Islamic websites is how to categorize them as Islamic websites. It is critical for the content to conform to Islamic ethics and principles. This study identifies a set of criteria for the literature for evaluating content of Islamic Websites. The criteria was used to evaluate Islamic websites. The user’s experiences, perceptions and expectations of Islamic website are analyzed and described.